MODEL SEKOLAH YANG MEMANUSIAKAN TINJAUAN TEORI STRUKTURAL KONFLIK - Ahmad Syauqi Fuady (STIT Muhammadiyah Bojonegoro, 2024)
Education becomes a class instrument in maintaining class position and status. The upper class has access and opportunities for quality education, something that is difficult for the middle and lower classes to obtain. Such an atmosphere, from a conflict perspective, will increasingly create gaps between classes and groups. Providing equal access and opportunities to obtain education in the Constitution is a state obligation. The community is also given the opportunity to get involved in the provision of education. It is important to offer alternative education in the form of schools with the perspective of humanizing humans according to their basic position so that they do not fall into the trap of thinking that education is only to meet the demands and competition for industrial interests and economic progress. A humanizing school at least tries to realize three things in the process and desired achievements. (1) Schools that educate character. Make character the main goal, as it is appropriate that the age of education is the same as the age of character education; (2) Schools that teach students to learn, not schools where teachers teach and students are taught; (3) Schools that liberate people from poverty and backwardness and are able to become a real ladder for each person to change their social status. Apart from that, it is also a school that is not separated from the environment in which it lives.